Comparative evaluation of antibacterial efficacy of nonantibacterial drugs - Diclofenac Sodium, Omeprazole and Cetirizine against E. faecalis when used as an intracanal medicament: An in vitro study - Dr. Prachi Patel,; Dr. Shraddha Chokshi,; Dr. Zarna Sanghvi,; Dr. Pooja Joshi,; Dr. Setu Kalaria,; Dr. Rinkal Virani, (The Bioscan, 2025)
Aim: This study aimed to evaluate the antibacterial efficacy of non-antibacterial drugs—diclofenac, omeprazole, and cetirizine—against Enterococcus faecalis when used as intracanal medicaments at time interval of 24 hr and 7 days in endodontic treatments. Settings and Design: An in-vitro comparative study Materials and Method: The study comprised of four test groups- Group – 1 [Ca (OH)2 (16mg/ml)], Group – 2 [Diclofenac sodium (400 mg/ml)], Group – 3 [Omeprazole (4 mg/ml)], Group – 4 [Cetirizine (2 mg/ml)], each group contained 10 samples, which were evaluated for antibacterial efficacy using agar well diffusion test. The experimental specimens were then placed on agar plates inoculated with E. faecalis, and the area of inhibition was calculated. Statistical analysis: Antibacterial efficacy was evaluated using multiple group comparison using One-way Anova, Posthoc Tukey test and Paired t-test. Results: All the experimental groups exhibited bacterial inhibition; however, group 2 exhibited highest antibacterial activity compared to group 1,3 and 4. Conclusion: This study demonstrates the promising antibacterial efficacy of non-antibacterial drugs, particularly diclofenac sodium, when used as intracanal medicament against Enterococcus faecalis, highlighting its potential as an effective alternative in endodontic treatments.